Fundamentos do novo-desenvolvimentismo brasileiro nos governos Lula e Dilma (2003-2014) - Crozatti, Rafael Oberleitner (2016)
The objective of this study is to analyze the Lula and Dilma (2003-2014) under the developmental theoretical framework. As justification for this research lies in the fact that the understanding of the economic policy in the Lula and Dilma has been intense debate target in the gym and in Brazilian society. The new developmentalism is an alternative to conventional orthodoxy surpassed in the 1990s and even the Old developmentalism, being associated with actions in the context of economic policy of the governments in question. Therefore, this work is organized methodologically as follows: (i) the first chapter, an introduction is to contextualize the research interest in its theoretical, political and economic aspects; (Ii) the second chapter reviews the theoretical foundations of Developmentalism, New developmentalism and Social developmentalism, (iii) the third chapter systematize the performance of the Brazilian economy in the Lula government (2003-2010) and Dilma (2011-2014) and as the main economic policies adopted by each government; (Iv) the fourth chapter develops a combination of theoretical elements presented in Chapter 2 with the analysis of the Brazilian economy (2003-2014) developed in chapter 3 in order to verify that the new developmentalist ideals are the real identity of this period in driving the economic policy of Lula and Dilma governments and finally; (V) the fifth chapter presents the final conclusions of the research carried out over the previous chapters. It appears pragmatically that the class coalition in Brazil today can not be understood as liberal-dependent as seen in the 1990s and mid-2000s, but it is early to say that it is a national-popular pact as presupposes New developmentalism. It appears pragmatically that the class coalition in Brazil today can not be understood as liberal-dependent as seen in the 1990s and mid-2000s, but it is early to say that it is a national-popular pact as presupposes New developmentalism. The Lula government, especially in the second term took the first steps on the path of building the developmental national pact, and the Dilma government sought more defined shape produce it in the first years in office.